HUBUNGAN PENGETAHUAN DAN SIKAP SISWA TERHADAP PENCEGAHAN PENGGUNAAN NARKOBA DI SMA NEGERI UNGGUL BINAAN BENER MERIAH TAHUN 2024 - Sari, Sukiyana; Saipullah; Pratama Putra, Andi (Akper Kesdam I/Bukit Barisan Padang, 2024)
ABSTRACTAccording to WHO, what is meant by NARKOBA is a substance that, when put into the body, will affect physical and psychological functions (except food, water, or oxygen). The number of Indonesia's population aged 15-64 years in the category of having used NARKOBA is 4,827,616 people and in the category of one year using NARKOBA is 3,662,646 people. The purpose of this study is to determine the relationship between knowledge and student attitudes towards the prevention of drug use at SMA Negeri Unggul Binaan Bener Meriah in 2024. This study uses the Simple Random Sampling method with a population of 126 students and a sample of 56 students. With a p value of 0.005 (p value = 0.05), the results of the study showed that there was a relationship between knowledge and the prevention of drug use. In addition, the attitude of preventing drug abuse is related to the value of p value = 0.009 (p value = 0.05). The conclusion in this study is that there is a significant relationship between knowledge and attitudes towards the prevention of drug use at SMA Negeri Unggul Binaan by Bener Meriah. Schools need to provide accurate and up-to-date information to their children about the dangers of DRUGS. Parents are also expected to teach healthy values, as well as be a good example in decision-making related to DRUGS.Keywords : DRUGS, Abuse, Attitudes, Knowledge